Inflammatory polyarthritis induced by nivolumab treatment in a patient with malignant melanoma: A case report (Annals of Medical Research, 2023)
Nivolumab is a monoclonal antibody that inhibits the programmed death ligand 1 from binding with PD-1 and restricts T-cell inactivation against cancer cells.After the introduction of nivolumab, in addition to its known side effects, its relationship with some rheumatic diseases has been reported, but it has not been clearly demonstrated.Here, we presented a case of inflammatory polyarthritis in a patient treated with nivolumab for malignant melanoma.This case resulted from the use of PD-1 blocker; It supports that we should be careful about rare side effects besides causing some adverse events due to autoimmune activation in patients.
Keywords: Melanoma; Nivolumab; Inflammatory polyarthritis